(untitled) (Asian Business Research, 2022)
There are many types of budgeting, and budgeting based on profit models is rare. This paper combines financial big data with management accounting methods to build a profit model in financial big data; and uses model data as the basis and basis for preparing flexible budgets, making budget preparation and execution more scientific and feasible; The company’s budget preparation method has been introduced; more importantly, financial accounting and management accounting are integrated, and the forecasting and budgeting functions of management accounting applications are really brought into play and applied.